Increased Enthesopathy in Patients With Familial Mediterranean Fever: Evaluation With a New Sonographic Enthesitis Index. (1st February 2013) - Ozkan, Fuat; Cetin, Gozde Yildirim; Inci, Mehmet Fatih; Bakan, Betul; Yuksel, Murvet; Ekerbicer, Hasan Cetin; Sayarlioglu, Mehmet
Abstract : Objectives: The aim of this study was to determine the frequency of enthesopathy in familial Mediterranean fever by using a newly developed sonographic method, the Madrid Sonographic Enthesitis Index (MASEI). Methods: The study included 50 consecutive patients with familial Mediterranean fever and 57 healthy sex‐ and age‐matched control participants. Six entheseal sites (olecranon tuberosity, superior and inferior poles of the patella, tibial tuberosity, and superior and inferior poles of the calcaneus) on both lower limbs were evaluated. All sonographic findings were identified according to MASEI. Validity was analyzed by receiver operating characteristic curves. P < .05 was considered significant. Results: Mean total enthesitis scores ± SD were 7.54 ± 4.99 for patients and 3.63 ± 3.03 for controls ( P < .001). No statistically significant correlation was found between the MASEI score and familial Mediterranean fever duration or colchicine treatment duration. There was no difference between the MASEI score and the presence or absence of arthritic involvement among the patients. The area under the receiver operating characteristic curve was 0.74 (95% confidence interval, 0.649–0.839). When analyzed by sex, men with familial Mediterranean fever had significantly higher MASEI scores than women ( P < .05). Conclusions: This study showed significant enthesopathy in patients with familial Mediterranean fever. The findings support the hypothesis that familial Mediterranean fever and spondyloarthropathy may have common inflammatory mechanisms and suggest that the MASEI scoring system can be incorporated into clinical protocols for studying patients with familial Mediterranean fever in daily practice.